EFFECTIVENESS OF TEACHER INNOVATION IN THE CHILDREN'S INDEPENDENCE AND FINE MOTOR ASPECT - Amelia, Najma; cinantya, celia (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2024)
The purpose of this research is developing children’s fine motor skills in cutting according to patterns through the DONAT model (Direct instructiON and media Awan pinTar). The approach used is a qualitative approach with the type of Classsroom Action Research which is held in three meetings. The research subjects were the children of group B TK Aisyiyah Bustanul Athfal 36 Banjarmasin in the 2022/2023 academic year, which consisted of 18 children. The results showed that the teacher’s activity at the 3rd meeting obtained a score of 27 and reached the Very Good criteria. The activity of the 3rd meeting children obtained a percentage of 94% and reached the criteria for All Active Children. The independence of the 3rd meeting children obtained a percentage 0f 83% and reached the criteria for All Independent Children. The results of the child’s fine motor development obtained a percentage of 83% and reached the Very Good Development criteria.